Assessment of radiation dose due to intake of uranium through groundwater and its carcinogenic and non-carcinogenic risks in southwest and northeast Punjab, India. Issue 7 (August 2018) - Saini, Komal; Duggal, Vikas; Bajwa, BS
This study was undertaken to assess uranium levels in drinking water along with carcinogenic and non-carcinogenic risks associated with its ingestion covering southwest and northeast regions of Punjab state, India. The uranium concentration in drinking water of southwest and northeast Punjab varied from 0.13 to 676 mg m −3 and 0.11 to 28.2 mg m −3 with mean values of 76.27 and 5.75 mg m −3, respectively. Thirty-five per cent (35%) of the analysed samples particularly from the southwest Punjab exceeded 60 mg m −3 Indian maximum acceptable concentration recommended by the Atomic Energy Regulatory Board, India. The measured annual effective doses ranged from 0.22 to 1136 µSv y −1 and 0.18 to 47.4 µSv y −1 for southwest and northeast Punjab, respectively. The mean hazard quotient for southwest Punjab was found to be greater than 1, indicating significant risk due to chemical toxicity of uranium which suggests the regular detailed monitoring of uranium content in groundwater samples is required from different depths following grid pattern. However, the uranium concentration with its both radiological and chemical risks in all the water samples from northeast Punjab was well below the recommended limits.